Pluralism and Justice beyond Political Liberalism - Fernández Manzano, Juan Antonio (Estudios de Filosofía, 2017)
The article seeks to address some aspects of the articulation between pluralism and justice. More specifically, the possibilities to delve into a theory of justice that is able to host within the same political framework citizens from heterogeneous cultures and values. This leads to highlight some of the shortcomings of the relativistic and monistic positions and to defend a position that starts from the position of political liberalism and goes beyond it, in order to lead to a political framework neither neutral nor perfectionist.